2018
DOI: 10.1111/bjd.16147
|View full text |Cite
|
Sign up to set email alerts
|

The association between atopic dermatitis and hand eczema: a systematic review and meta-analysis

Abstract: Important study limitations include the wide use of questionnaire studies, and lack of prospective studies as well as poor clinical phenotype descriptions. In conclusion, our systematic review and meta-analysis showed that patients with AD had a strongly increased prevalence of HE. Clinicians should continue to guide patients with AD away from occupations with a high risk of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 70 publications
(122 reference statements)
4
35
1
3
Order By: Relevance
“…found that patients with atopic dermatitis had a 3-4-fold increased prevalence of HE compared with controls. 84 Accordingly, the pooled proportion of adults with HE and a history of atopic dermatitis found in this meta-analysis reached 34.4%, with significantly higher estimates for children and adolescents (79.9%).…”
Section: Duration Eruptions and Age At Onset Of Hand Eczemamentioning
confidence: 62%
“…found that patients with atopic dermatitis had a 3-4-fold increased prevalence of HE compared with controls. 84 Accordingly, the pooled proportion of adults with HE and a history of atopic dermatitis found in this meta-analysis reached 34.4%, with significantly higher estimates for children and adolescents (79.9%).…”
Section: Duration Eruptions and Age At Onset Of Hand Eczemamentioning
confidence: 62%
“…However, a population-based twin study demonstrated that the heritability of HE was not explained by AD (Lerbaek et al, 2007). A meta-analysis of 26 studies found that AD was significantly associated with an increased prevalence of HE using point prevalence (odds ratio Ruff et al, 2018).…”
Section: Pathogenesismentioning
confidence: 99%
“…Endogene risikofaktorer omfatter forandringer i hudbarrieren som for eksempel atopisk eksem (7,8). Mutasjon i genet for filaggrin, et barriereprotein i huden, er en risikofaktor både for atopisk eksem og kronisk håndeksem (9).…”
Section: Klinisk Bilde Risikofaktorer Og Inndelingunclassified